Job satisfaction among nurses in private hospital in Johor Bahru, Malaysia - Natchetiraammal, Bala (2021)
The purpose of this study to examine the relationship and effect of career development, education opportunity, working environment and workload to job satisfaction among nurses in private hospital in Johor Bahru. This is a quantitative study, and six hypotheses were developed. The questionnaire was developed from previous study and pilot tested. Due to Covid19 pandemic and Movement Control Order (MCO), the questionnaire was distributed online to the target respondents. A total of 264 feedback were received back. The normality, reliability, univariate, bivariate and multivariate statistical analysis was conducted on the data using the Statistic Package for Social Science (SPSS) version 25. All hypotheses are accepted. Education opportunity is the most influential variable, followed by workload and working environment on job satisfaction among nurses in the private hospital in Johor Bahru. It is recommended that future research should cover a larger sample.